The principle of subsidiarity and its enforcement in the EU legal order : the role of national parliaments in the early warning system - Granat, Katarzyna <<[VerfasserIn]>> (Hart, 2018)
The subsidiarity principle in the EU treaties -- The involvement of national parliaments and the EWS -- The scope and application of the EWS -- Design of the subsidiarity review at the national level -- The EWS within national political systems
Bibliographie: Seite [241]-252
Revised and updated version of the author's PhD